Prevalence and Management of Pestalotia Leaf Spot (Pestalotia sp.) of Strawberry - Rajnish, K.; Gautam, H. R. (International Journal of Economic Plants, 2022)
Pestalotia leaf spot was prevalent in all the locations at Solan and Sirmour districts of Himachal Pradesh during 2017−18 cropping season. The disease incidence of Pestalotia leaf spot ranged from 6.53 to 22.87% and severity ranged from 4.44−17.77% respectively. In Solan district, highest incidence (22.21) and severity (16.66%) were recorded at Nauni followed by Mandholghat with incidence of 20.25% and disease severity of 13.33% respectively. Whereas, in Sirmour district, highest incidence (22.87%) and severity (17.77%) of Pestalotia leaf spot was recorded at Dhaulakuan and lowest incidence (6.53%) and severity (4.44%) was recorded at Baghthan. Overall data revealed that the incidence and severity of the leaf spot was higher in Solan district than Sirmour district. Among different fungicides evaluated under in vitro conditions, carbendazim was found most effective with 98.49% of mycelial inhibition followed by mancozeb (96.60%) and copper oxy chloride (94.60%). Under field conditions, minimum disease incidence (4.72%) and disease index (1.84%) were recorded in treatment with sprays of Bavistin. Sprays with Diathane M-45 were found next in efficacy with disease incidence of 5.14% and disease index of 2.48%.